Impact of Trade Union in the Hotel Workers - Baral, Uma Nath (Journal of Political Science, 2018)
Along with the implementation of democracy, Nepalese people are privileged of having different categories of human rights. Among them, trade union is one of the major political rights. The workers in industry, trade, business and other labour markets are organized within the trade union. Hotels are supposed to be the service industry or business organizations that are foundincreasing rapidly in the post 1990’s democratic era. Hence, in this post-republican democracy along with settlement of the Maoist arms conflict, hotel business seems to be blooming. In order to be successful in the hotel business, it requires skilled manpower for providing good services. Skillful labourers require having basic rights with several privileges only then they can be fully devoted and committed to their profession, which may lead to a successful hotel business. Pokhara is a renowned place for tourism and hotel business. There are around one thousand hotels here including stars and non-stars. There are different trade unions for organizing the hotel workers for their rights. Whether such unions are working for seeking more privileges to their members is a major question for research. In this regard, to study the role and impact of trade unions among the hotel workers in Pokhara is the main objective of this research paper. Two hotels as one from stars and another from non-stars were chosen for obtaining the required data for the fulfillment of the objective. As with the opening of trade unions - 144 - in almost every sector of industry, including the hospitality, the rights of the labour are taken into considerations. Being united under the trade unions, workers are obtaining various facilities as job security, allowances and basic salary as prescribed by the governmental rules. It has been found that many workers have positive attitudes towards trade unions and the managements have also been positive towards workers as well as unions. Most of the workers enjoy the union memberships and participate in the union activities. But some of them are not satisfied with union activities, because they believe the leaders are more guided and directed by their self-interests and their affiliated political parties. However, as per workers perspective there is cooperative relationship between trade unions and hotel management in fulfillment of their basic and other rights. Journal of Political Science, Volume XVIII, 2018, Page : 143-166